WAIS Divide Ice Core Images, Antarctica - Mcgwire, Kenneth Christian (IEDA: US Antarctic Program Data Center, 2010)
Abstract: This data set is comprised of optical images of ice core sections, acquired with a digital line-scan camera in the cold room facility at the U.S. National Ice Core Laboratory (NICL). Ice core sections are archival cuts which have rough-out rounds of ice with a single plane cut along one side. Ice sections were illuminated with fiber optic light guides connected to a 1000 watt (W) xenon light source. Original scan resolution varies from about 0.05 mm to 0.1 mm, and is documented in the metadata for each image. Images are in uncompressed Tagged Image File (.tif) form, with resolutions of 1.0 mm and 0.1 mm. Depth of image in the ice core is documented in the metadata files for each image. Data are available via FTP as .tif image files. Supporting information is available as ASCII text files (.txt), and other file formats readable with a freely available image processing program, IceImageJ.